The Impact of Lead (Pb) on Health - Maria, Hana; Jessica, Alicia; Gabriella, Evelyn; Aprillia, Christine; Yudiarso, Ananta (Journal of Global Research in Public Health, 2025)
This  systematic  literature  review  aims  to  evaluate  the neurodevelopmental, behavioral, and physiological impacts of lead (Pb) exposure in both children and occupationally exposed populations. Using the PRISMA framework, we reviewed 13 peer-reviewed studies published between 2013 and 2023. The studies include a range of methodologies- longitudinal, cross-sectional, experimental, and systematic reviews assessing lead exposure’s health effects. Databases were screened based on inclusion criteria focused on cognitive, behavioral, or physiological outcomes linked to lead levels in blood or tissues. Across studies, childhood lead exposure was consistently associated with lower intelligence scores, behavioral disorders (e.g., aggression, hyperactivity, depression), and increased risks for mental health conditions. Occupational exposure, particularly among gas station workers and forecourt attendants, was linked to chronic fatigue, sleep disturbances, and potential neurodegenerative conditions like ALS. The neurotoxic mechanisms included oxidative stress, neurotransmitter disruption, and long-term accumulation in bones. Notably, even low-level lead exposure resulted in significant adverse effects, with no safe threshold identified. These findings underline the critical need for public health interventions including environmental regulation, routine blood lead screening, protective workplace protocols, and early childhood monitoring. Prevention and awareness programs are essential to reduce lifelong harm from lead exposure, particularly in vulnerable populations.